2022
DOI: 10.1007/s12144-022-03520-1
|View full text |Cite
|
Sign up to set email alerts
|

Parental stress and child mental health: a network analysis of Romanian parents

Abstract: Parental stress is related to child mental health problems, with numerous evidence indicating that it is an important predictor of parenting and parent-child relationship. New approaches to psychopathology could be particularly informative for clinical research, however, there is limited research that employs network analysis with parents. Network analysis could contribute to a better understanding of the relationship between child mental health problems and parental stress by highlighting the most central nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The finding of the current study revealed that there was a high statistically significant relation between total mental health score and work stress reported by the participating parents. This result was supported by [17,41]. This could be due to the daily life pressures, problems, and challenges faced by working mothers and fathers who spend a long period of time at work and return home full of fatigue, exhaustion, and negative energy that is unconsciously projected onto the children without spending a longer period of time with their children, especially, which negatively affects the mental health of children.…”
Section: Concerning Relation Between Parent Characteristics and Total...mentioning
confidence: 76%
“…The finding of the current study revealed that there was a high statistically significant relation between total mental health score and work stress reported by the participating parents. This result was supported by [17,41]. This could be due to the daily life pressures, problems, and challenges faced by working mothers and fathers who spend a long period of time at work and return home full of fatigue, exhaustion, and negative energy that is unconsciously projected onto the children without spending a longer period of time with their children, especially, which negatively affects the mental health of children.…”
Section: Concerning Relation Between Parent Characteristics and Total...mentioning
confidence: 76%
“…44 Moreover, our ndings, in harmony with previous ones, revealed a strong correlation between parental stress and elevated anxiety in children. 45 The stress experienced by parents, whether it was caused by nancial, health, work or relationship issues, may impact the child's emotional well-being, sense of security and ability to cope with stressors. 46 In addition to parental depression and stress, we concluded an association between parental anxiety and increased anxiety in children, a result that was highlighted by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that parent and child nodes that exhibited the highest centrality and bridge centrality could predict treatment response (Hagan et al, 2023; Monteleone et al, 2023). In another study of parent–child dyads, Păsărelu et al (2023) found that parents’ perceived coping bridged parental stress with child mental health symptoms, suggesting that parental stress may be an important target of intervention programs. The inclusion of parental nodes provides critical information about child symptoms, as well as psychopathology across the dyad, which could inform intervention design and measurement of treatment outcomes.…”
Section: Symptom Network Analysismentioning
confidence: 99%